(untitled) (Journal of Surgical Sciences, 2019)
Bezoars are retained concretions of undigested foreign material that accumulate and coalesce within the gastrointestinal tract, commonly in the stomach .The occurrence of bezoars formation is well documented in human, but the diagnosis, management and treatment remains a difficult task for the patient and health care professionals. The differential diagnosis of upper GIT obstruction in children includes both common and rare pathologies. Within these lists different types of bezoars causing upper GIT obstruction have been reported in. literature and different methods of management have been described. In this article we ltave reported that a 6 years old boy presented to us with features of duodenal obstruction .The clinical and radiological evaluation was suggestive of duodenal obstruction. Finally, laparotomy was done and a phytobezoar found in the third part of duodenum which was disimpacted and removed by gastrotomy. The child had an uneventful post o.perative course and discharged on the seventh post operative day in a stable condition. Journal of Surgical Sciences (2012) Vol. 16 (2) : 98-100